EasyA: Easy and effective way to generate pairwise test data - Rabbi, Khandakar Fazley; Sabira, Khatun; Che Yahaya, Yaakub; Klaib, Mohammad F. J. (IEEE, 2013)
Testing is a very important task to build error free software. As the resources and time to market is limited for a software product, it is impossible to perform exhaustive test i.e., to test all combinations of input data. To reduce the number of test cases in an acceptable level, it is preferable to use higher interaction level (t way, where t = 2). Pairwise (2- way or t = 2) interaction can find most of the software faults. This paper proposes a matrix based calculation for pairwise test data generation algorithm named EasyA to optimize the number of test cases. Java program has been used to test the performance of the algorithm. The performance is better than the existing algorithms/tools in terms of number of generated test cases and time consumption.